ADULT ATTACHMENT STYLES AND COMMUNICATION STYLES AMONG TRAINEE COUNSELLORS - Jue Xin, Lim (Universiti Malaysia Sarawak (UNIMAS), 2020)
The counselling process involves a lot of communication between the counsellor and client, therefore it is important to know whether attachment style of the counsellor will affect the way he or she communicates, as it may influence the therapeutic process. This study investigated the relationship between adult attachment styles and communication styles among trainee counsellors. Data on all second year counselling students (N=60) from Universiti Malaysia Sarawak were analyzed using Spearman correlation analysis and one-way Analysis of Variance (ANOVA). Findings show securely-attached trainee counsellors are nicer when they communicate, while for those with fearful attachment, they tend to be emotional and less precise when they communicate. On contrary with the previous researches, it was found that dismissing individuals are expressive, reflective, and nice in communication. These results highlight the importance of having trainee counsellors to be aware of their own attachment styles, then moving on to self-improvement continuously, in order to facilitate better help for the clients.